Biosimilars and the Patent Law - Świerczyński, Marek; Więckowski, Zbigniew (Medicine, Law & Society, 2019)
Biopharmaceuticals are one of the most important recent medical innovations which revolutionised many areas of medicine. Dynamic development of the market for biopharmaceuticals in recent years is related to the expiration of the IP exclusive rights on original innovative biological medicinal products. This has resulted in introduction to the market of biosimilars. One of the greatest challenges concerning the emergence of biosimilars is modifying the law to ensure balance between the market development of biosimilars and access of patients to biological therapy. The development of biopharmaceutical inventions works hand in hand with the patent system. It should be underlined that IP rights in the biopharmaceutical sector are crucial for promoting innovation due to the very long time of product development. It is exactly the area in which patents make sense to fill the gap between innovation and the risk of imitation. However, the existing patent system is too expensive and slow for biotechnology development. It should be further adapted to the needs of biopharmaceuticals.